ALUMNI NETWORKS AND ECONOMIC REINFORCEMENT IN PESANTREN UMMUSSABRI - Jalil, Abdul (Shirkah: Journal of Economics and Business, 2019)
This study discusses the alumni network supporting the economic development of an Islamic institution, namely pesantren. In general, the strong alumni networks lead to strengthening the successful economic sector in the pesantren, since the alumni have a sense of belonging to pesantren. This study focuses on how alumni network contributes significantly to the development of business units in Pesantren Ummussabri, Kendari. Doing participatory observation and in-depth interviews, the study had been conducted in Pesantren Ummusabri, particularly in Empang 99 Paleppo unit. Such information had been gathered from the administrator for pesantren?s business division, alumni coordinator and some informants of Empang 99 Paleppo business unit.  This study elucidates that a strong pesantren alumni network can improve the pesantren creatively. It clearly can be seen from how the alumni, who have successfully occupied important positions in the government, have established Empang 99 Paleppo. Keywords: alumni network, pesantren, creative economics, Kendari